Production management model to increase efficiency in the cotton garment manufacturing process applying MPS kaizen and SMED tools in a SME in the textile sector - Naranjo Torres, Juan Sebastian (2025)
This research project focuses on enhancing manufacturing efficiency through the application of Master Production Schedule (MPS), KAIZEN, and Single Minute Exchange of Die (SMED) tools. The company's initial efficiency level of 58.8% is attributed to factors such as a lack of trained personnel, absence of a requirements plans, and wastage of raw materials, primarily due to insufficient inputs during production. To address these issues, the project measured key indicators such as efficiency level, effective production hours, and raw material waste. The engineering tools MPS, KAIZEN, and SMED were then employed to create a production and supply tool, implement training plans for operators to reduce losses and reprocessing, and redesign the workshop layout to decrease production times and achieve line production. During the initial two months of implementation (August and September 2023), the project successfully increased the average production efficiency to 76.79%, reduced raw material waste to 2.11 kg per day on average, and extended the effective production time to 7.08 hours per day. The economic benefits of the project were realized, with a 6-month projection demonstrating positive results. In a pessimistic scenario, the net present value (NPV) was only $1487.38 lower than without project implementation. In a normal scenario, the project yielded impressive results, including an NPV of $15 385.67, an internal rate of return (IRR) of 69%, a benefit-cost ratio (B/C) of 4.5, and a payback period of one month and 15 days.